Spinal NLRP3 inflammasome activation mediates IL-1β release and contributes to remifentanil-induced postoperative hyperalgesia by regulating NMDA receptor NR1 subunit phosphorylation and GLT-1 expression in rats. (31st October 2022) - Yuan, Yuan; Zhao, Yue; Shen, Mengxi; Wang, Chenxu; Dong, Beibei; Xie, Keliang; Yu, Yang; Yu, Yonghao
Background: Trafficking and activation of N-methyl-D-aspartate (NMDA) receptors play an important role in initiating and maintaining postoperative remifentanil-induced hyperalgesia (RIH). Activation of the NOD-like receptor protein 3 (NLRP3) inflammasome has been linked to the development of inflammatory and neuropathic pain. We hypothesized that activation of NLRP3 inflammasome mediates IL-1β release and contributes to RIH in rats by increasing NMDA receptor NR1 (NR1) subunit phosphorylation and decreasing glutamate transporter-1 (GLT-1) expression. Methods: Acute exposure to remifentanil (1.2 μg/kg/min for 60 min) was used to establish RIH in rats. Thermal and mechanical hyperalgesia were tested at baseline (24 h before remifentanil infusion) and 2, 6, 24, and 48 h after remifentanil infusion. The levels of IL-1β, GLT-1, phosphorylated NR1 (phospho-NR1), and NLRP3 inflammasome activation indicators [NLRP3, Toll-like receptor 4 (TLR4), P2X purinoceptor 7 (P2X7R), and caspase-1] were measured after the last behavioral test. A selective IL-1β inhibitor (IL-1β inhibitor antagonist; IL-1ra) or three different selective NLRP3 inflammasome activation inhibitors [(+)-naloxone (a TLR4 inhibitor), A438079 (a P2X7R inhibitor), or ac-YVADcmk (a caspase-1 inhibitor)] were intrathecally administered immediately before remifentanil infusion into rats. Results: Remifentanil induced significant postoperative hyperalgesia, increased IL-1β and phospho-NR1 levels and activated the NLRP3 inflammasome by increasing TLR4, P2X7R, NLRP3, and caspase-1 expression, but it decreased GLT-1 expression in the L4-L6 spinal cord segments of rats, which was markedly improved by intrathecal administration of IL-1ra, (+)-naloxone, A438079, or ac-YVADcmk. Conclusion: NLRP3 inflammasome activation mediates IL-1β release and contributes to RIH in rats by inducing NMDA receptor NR1 subunit phosphorylation and decreasing GLT-1 expression. Inhibiting the activation of the NLRP3 inflammasome may be an effective treatment for RIH.